Relevansi Pemikiran Yūsuf al-Qaradāwī terhadap Perilaku Konsumsi - Arifin, Bustanul; Ulumuddіn, Moh. (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2024)
Background. According to al-Qaradāwī, Islam stipulates that spending wealth must not: exceed necessary limits, and; being too frugal, not because you can't afford it, but because you're being naughty. Islam teaches consumers to be simple. Aims. This study examines al-Qaradāwī's thoughts on consumption behavior. Methods. This library research uses a theological-philosophical approach to measure al-Qaradāwī's legal istimbath method. Data was collected using documentation techniques. Content analysis was carried out qualitatively using the descriptive-analytic method. Results. Regulation of consumption behavior according to al-Qaradāwī is not being stingy or bakhil, not being wasteful and being modest. Implementing al-Qaradāwī's thoughts about not being stingy or stingy means giving donations, both obligatory and sunnah, both for oneself and for the family, for society and for fi sabilillah (in the way of Allah). Not being stingy or stingy means that humans should be fair in using wealth. Not being wasteful means not spending wealth on something that has no benefit and on something that is forbidden, including spending wealth excessively, that is, exceeding the limit in terms of things that are halal. Simplicity must be instilled in every human's daily life, namely an attitude that is in the middle between an attitude of servility, a wasteful attitude, and an excessive attitude, including an attitude of luxury. Spending wealth for needs and pleasures in Islam is not prohibited, but needs and pleasures must be in accordance with abilities and according to what is needed.